Perbandingan Keluhan Low Back Pain pada Pekerja Batik Tulis dan Cap di Kecamatan Danau Teluk Kota Jambi Tahun 2020 - Entianopa, Entianopa; Wulan, Meisi; Hilal, Samsul (Indonesian Journal of Health Community, 2020)
Low Back Pain (LBP) is a musculoskeletal disorder resulting from wrong ergonomics. The exact incidence of LBP in Indonesia, namely 7.3% of LBP cases, is not caused by organic abnormalities, but by an incorrect position of the body at work. One of the jobs that created LBP was batik craftsmen. This study aims to determine the comparison of complaints of low back pain in written and stamped batik workers. This research is a cross sectional quantitative research design. The population of this research is all batik workers, amounting to 74 people. The sample in this study amounted to 48 people with a purposive sampling technique. The results of univariate analysis showed that there were 27 (56.2%) respondents aged ?35 years, there were 25 (52.1%) respondents have a working period of ? 10 years, there are 13 (54.4%) respondents who have written batik experiencing low back pain at levels 1-3 and there are 16 (66.7%) respondents who have written batik experiencing low back pain at levels 1-3 . The results of the bivariate analysis showed that there was a difference between complaints of low back pain in batik workers and printed batik and there was a relationship between age and years of service with the incidence of LBP among batik workers.